Grief tied to Death: Influence of the experience of severe grief on the development of diseases of the cardiovascular system - Gryshchenko, Pavel (Psychosomatic Medicine and General Practice, 2018)
Influence of the experience of severe grief on the development of diseases of the cardiovascular system.